Developing and testing a Turkish version of Torrance's tests of creative thinking: A study of adults - (:unkn) unknown (Creative Education Foudation, 2006)
The present study had two purposes. The first was to translate one of the most popular creativity measures in the West, the Torrance Tests of Creative Thinking, into Turkish and to check the equivalency of the Turkish version against the original English measure. The second, after developing an equivalent form of the TTCT in Turkish, was to compare the creative abilities of an adult Turkish sample, as measured by the Turkish TTCT, against data collected in the united States. All four formats of Torrance's tests were translated into Turkish and evaluated for reliability and equivalency. Students in an English Language Teachers program completed both the original version of the TTCT and the newly translated Turkish version. Analysis of their scores showed a high degree of correspondence between the two language versions. Afterwards, the Turkish TTCT was used to collect data from more than 800 research participants. A cross-cultural comparison was made to data previously collected in the united States. A number of significant differences emerged between the Turkish and united States samples, such as Verbal Fluency, Verbal Originality, and Abstractness of Titles. These and other results are discussed, such as a comparison between males and females in the Turkish sample.